Factors Affecting the Incidence of Hypertension in Women of Childbearing Age - Liliek Pratiwi; Rusmiyati Rusmiyati; Danny Putri Sulistyaningrum; Widya Mariyana; Yani Nurhayani; Aticeh Aticeh (International Forum of Researchers and Lecturers, 2025)
Hypertension, acommonand chronic non-communicable disease, has become a global health problem and aleading cause of death. Blood pressure that exceeds normal values is known as hypertension, or high blood pressure. From this theory, this study aims to assess the relationship between obesity and family history factors that affect hypertension in women of childbearing age. This study used quantitative methods with an observational analytic design cross-sectional approach. The selected population was women aged 15 to 45 years Getakmoyan village. The result, because the ρ value is greater than α = 0.05. The results showed that 16 respondents who were obese and had hypertension had a ρ value of 0.007 (α = 0.05 because the ρ value was smaller than α). Overall, lifestyle factors such as obesity and diet have a greater influence than family history on the risk of hypertension in women of childbearing age.